Does Religiosity Matter? Experimental Research on Abusive Supervision in Budgetary Slack Creation - Yenni Agustina; Yunia Amelia; Aryan Danil Mirza BR (The Indonesian Journal of Accounting Research, 2022)
Abusive supervision behavior has long been a problem in the budgeting process. Its nature has been proven to damage individuals and significantly impact the corporate environment. Several studies related to Abusive supervision show evidence that individuals who experience abusive supervision tend to do Budgetary Slack. Meanwhile, religiosity, which is predicted as a personal value that can control individuals from committing acts outside the norm or harming the company, sometimes has little effect. Several studies have shown that high religiosity does not prevent individuals from taking despicable actions such as earnings management, Budgetary Slack, commitment escalation, and others. Is there anything wrong with religiosity as an individual's value? Does this occur due to variable measurement error (instrument) or method bias in sampling? Researchers tried to compare various instruments related to religiosity to obtain the most appropriate measurement, especially by photographing this phenomenon. We surveyed 83 participants using the experimental method with a 2x2 factorial design to understand how religious belief might buffer against the destructive effects of abusive supervision on budgetary slack. The results of this study are expected to be a reference (empirical evidence) related to the role of religiosity as a personal value in preventing destructive behavior of individuals, especially in the budgeting process.